Three-Phase Handover Management and Access Point Transition Scheme for Dynamic Load Balancing in Hybrid LiFi/WiFi Networks - Murad S.S.; Yussof S.; Hashim W.; Badeel R. (MDPI, 2023)
Data transfer; Decision making; Economic and social effects; Information management; Intelligent systems; Monte Carlo methods; Optical gain; Quality of service; Resource allocation; Wi-Fi; Wireless local area networks (WLAN); Data-rate; Energy; Hand over; Handover management; Hybrid network; Lifi; Load-Balancing; Three phase; Three phasis; Wireless communications; MATLAB